Revenue-constrained strategic trade and industrial policy - Leahy, D; Neary, J (Elsevier, 2004)
We characterise optimal revenue-constrained trade and industrial policy towards dynamic oligopolies, prove that total net subsidy payments at the optimum are decreasing in the social cost of funds, and illustrate the implications in Cournot and Bertrand special cases.